Blendas e filmes de galactomanana e xiloglucana: caracterização físico-química - Mendes, Francisco Rogênio da Silva (2015)
Plant hemicelluloses have been widely used in the industry due to their ability to form edible and biodegradable films with glycerol as plasticiser. This work aimed to obtain hemicellulose-based films using Caesalpina pulcherrima and Tamarindus indica seeds as sources, also to evaluate the physicochemical properties of these blends. Both hemicelluloses were obtained by aqueous extraction followed by ethanol precipitation. T. indica and C. pulcherrima seeds showed yields of 25% and 20% galactomannan (GalCp) and xyloglucan (XilTi), respectively. The XilTi showed the lowest content of nitrogen related to proteins, as those are the most contaminant in these extractions. On the other hand, xyloglucans showed the highest ash content when compared to galactomannans. Through GPC the estimated molecular weight was 4.35 x 106 g / mol and 2.03 x 106 g / mol for GalCp and XilTi, respectively. The mannose / galactose ratio for GalCp was determined by 1H NMR 2.52: 1. Glucose / xylose / galactose ratio for XilTi was obtained by 13C NMR (2.6: 2.4: 1). All blends solutions showed a nonlinear relationship between the shear stress and the strain rate at 25 °C, presenting a non-Newtonian behaviour. FTIR revealed absorptions in the range 3000-3500 cm-1 typical for carbohydrates, concerning to the vibrational stretch (OH) bands in the range of 2926-2899 cm-1 attributed to symmetric and asymmetric vibrations of the grouping CH. Also, the bands at 815 cm-1 and 872 cm-1 were detected which refer to the stretch of the anomeric conformations of polysaccharides, α-D-galactopironose and β-D-mannopyranose, respectively. The FTIR spectrum for xyloglucan apart from the bands at 3000-3500 cm-1 and 2926-2899 cm-1, showed bands at 820 cm-1 and 870 cm-1 which are attributed to stretching of the links in α-D-xylose and β-D-galactose monosaccharides. Moreover, it was detected absorptions around 800-1200 cm-1 which are specific for xyloglucan polysaccharides. The obtained films by casting method showed no significant difference between their thicknesses and showed water vapour permeability ranging from 1,604 to 2,474 (g.mm/h.KPa.m). Through atomic force microscopy over the surface of the films, parameters such as texture, waviness and roughness were estimated. All blend-based films presented low irregular surfaces. In sum, the films and blends based on plant cell wall polysaccharides reserve is promising due to its biodegradability and come from renewable sources.